2018
DOI: 10.1155/2018/6835751
|View full text |Cite
|
Sign up to set email alerts
|

Body Image of Highly Trained Female Athletes Engaged in Different Types of Sport

Abstract: Background The aim of the study was to evaluate differences in body image across different types of sports in highly trained female athletes. Methods 242 female individuals, aged 13–30 years (M = 20.0, SD = 4.5), representing aesthetic sports (n = 56) and nonaesthetic sports (n = 186), were recruited from different sports clubs in Poland. Body image, BMI, age, the level of competition attained, and the training background of participants were recorded. Results One-way ANOVA showed differences in the body image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 47 publications
7
50
0
3
Order By: Relevance
“…The most curious data in our study is that self-esteem was higher in athletes than in the control group and better in gymnasts than in footballers. These results are in line with other researches [ 92 , 93 ], pointing out the importance of the practice of sport and of the type of sport, because self-esteem is different in aesthetic sports than in non-aesthetic sports, like football. Self-esteem is probably a protective factor to develop an eating disorder despite perfectionism, which is the most predictive variable as the multiple linear regression showed, and this variable was high in athletes.…”
Section: Discussionsupporting
confidence: 92%
“…The most curious data in our study is that self-esteem was higher in athletes than in the control group and better in gymnasts than in footballers. These results are in line with other researches [ 92 , 93 ], pointing out the importance of the practice of sport and of the type of sport, because self-esteem is different in aesthetic sports than in non-aesthetic sports, like football. Self-esteem is probably a protective factor to develop an eating disorder despite perfectionism, which is the most predictive variable as the multiple linear regression showed, and this variable was high in athletes.…”
Section: Discussionsupporting
confidence: 92%
“…An athlete may frequently have separate body images; an athletic body image and a social body image. 68–71 There may be tensions between the socially desirable body image and the ideal physique for performance in the athlete’s sport. 72 Both male and female athletes may have a body image that is in conflict with cultural norms and gender stereotypes.…”
Section: Preventionmentioning
confidence: 99%
“…A meta-analysis showed that athletes in general had a more positive body image when compared to non-athletes although the effect size is small (Hausenblas & Downs, 2001). However, other studies have noted that although athletes engage in high levels of physical activity, they can also report body image dissatisfaction depending on the type of sport (Abbott & Barber, 2011;Hulley & Hill, 2001;Kantanista et al, 2018;Nerini, 2015;Swami et al, 2009). As such, it is evident that the relationship between physical activity and body image satisfaction is neither simple nor direct.…”
Section: Literature Reviewmentioning
confidence: 99%